Influence of temperature and pH on polyacrylamide-based drilling fluid: Characterization and rheological study - Koh, Jin Kwei; Lai, Chin Wei; Johan, Mohd Rafie; Gan, Sin Seng; Chua, Wei Wei (European Journal of Chemistry, 2023)
Polyacrylamide (PAM) is a biodegradable polymer with good lubricity in friction reduction. However, there is insufficient guidance on the dosage of PAM and poor rheological information on the effects of temperature and pH. This study aimed to investigate the characterization of the material and rheological analysis regarding the effects of concentration, pH, and temperature of PAM. In material characterization, PAM has been shown to offer hydrophilic surfaces. In a rheological study, 1000 ppm PAM was the critical association concentration, as the rheological properties below 1000 ppm PAM were superior. This was due to the dispersion stability effect caused by the polymer concentration. Additionally, a low concentration of polymer contributes to bridging flocculation with an unstable rheological profile and low association networking. When the polymer concentration is further increased to the saturated adsorption level, the rheological profile of PAM above 1000 ppm is significantly affected as a result of the alternation from steric stabilization to depletion flocculation in a polymer system. Furthermore, the rheological performance of PAM was significantly affected by temperature and pH, showing better performance after heating to 60 °C and at pH = 10. Future studies can further develop modified PAM with specific additives at an optimized temperature and pH to investigate the rheological performance of drilling.